Zur Bekämpfung von Marktmachtmissbrauch in digitalen Märkten – Wettbewerbspolitische Maßnahmen im Vergleich - Miftari, Ardita

Of the efficacy of competition law in dealing with challenges of digital markets - Selected cases of Facebook - Minhaj, Noor

On the Efficacy of EU Competition Policy in the Context of Big Data - Rayhan, Md. Sashi

On the privatization of hospitals - The case of Germany - Busch, Anna Lisa

Der Marktplatz von Amazon - Eine wettbewerbspolitische Analyse - Kuzuoglu, Muhammed Numan

Zu den Auswirkungen von Big Data auf personalisierte Angebote in digitalen Märkten - eine wettbewerbspolitische Analyse - Sowinski, Olivia

Zu den Vor- und Nachteilen von Luftfahrtallianzen - Eine wettbewerbspolitische Perspektive auf den Alleingang von Emirates - Schmidt, Thomas

An Economic Analysis of Mergers and Aquisitions - The case of Facebook and WhatsApp - Yeboah, Amoabeng

Zu Online-Vergleichsportalen und deren Auswirkungen auf den Markt - Eine wettbewerbspolitische Analyse - Hensel, Jason

The Impact of Product Differentiation on Retail Bundling in a Vertical Market - Endres-Fröhlich, Angelika Elfriede; Hehenkamp, Burkhard; Heinzel, Joachim
We study the effects of product differentiation on the bundling incentives of a two-product retailer. Two monopolistic manufacturers each produce a differentiated good. One sells it to both retailers, while the other only supplies a single retailer. Retailers compete in prices. Retail bundling is profitable when the goods are close substitutes. Only then is competition so intense that the retailer uses bundling to relax competition both within and across product markets, despite an aggravation of the double marginalization problem. Our asymmetric market structure arises endogenously for the case of close substitutes. In this case, bundling reduces social welfare.
Keywords: Retail bundling; upstream market power; double marginalization; product differentiation

Manipulation durch Fake-Bewertungen: Einfluss von Such- und Erfahrungsgütern auf das manipulative Verhalten des Verkäufers - N., N.

An Analysis of Coalition Formation Methods to achieve Maximum Social Surplus - N., N.

Die Möglichkeiten der Blockchain-Technologie im Supply Chain Management - eine spieltheoretische Analyse - N., N.

Kindergarten Allocation and the Tradeoff between Stability and Diversity Considerations - N., N.

Effect of the Agent's bargaining positions in the efficiency of matching markets - N., N.

Stabile Zuordnung mit Paaren - Der neue NRMP Algorithmus - N., N.

School choice with reserves and quotas - N., N.

Organisation von Zeitbörsen - N., N.

Wage Bargaining and Employment Revisited: Separability and Efficiency in Collective Bargaining - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya (Scandinavian Journal of Economics)
We analyse the two-dimensional Nash bargaining solution (NBS) by deploying the standard labour market negotiations model of McDonald and Solow (1981). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems, such that the two solutions together replicate the solution of the two-dimensional problem if the NBS is applied. The axiom of Independence of Irrelevant Alternatives is shown to be crucial for this type of decomposability. This result has significant implications for actual negotiations because it allows for the decomposition of a multi-dimensional bargaining problem into one-dimensional problems---and thus helps to facilitate real-world negotiations.
Keywords: Labour market negotiations; efficient bargains; Nash bargaining solution; sequential bargaining; restricted bargaining games

Socio-legal systems and implementation of the Nash solution in Debreu–Hurwicz equilibrium - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)
Abstract In this article we combine Debreu’s (Proc Natl Acad Sci 38(10):886–893, 1952) social system with Hurwicz’s (Econ Design 1(1):1–14, 1994; Am Econ Rev 98(3):577–585, 2008) ideas of embedding a “desired” game form into a “natural” game form that includes all feasible behavior, even if it is “illegal” according to the desired form. For the resulting socio-legal system we extend Debreu’s concepts of a social system and its social equilibria to a socio-legal system with its Debreu–Hurwicz equilibria. We build on a more general version of social equilibrium due to Shafer and Sonnenschein (J Math Econ 2(3):345–348, 1975) that also generalizes the dc-mechanism of Koray and Yildiz (J Econ Theory 176:479–502, 2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (Designing rights: invisible hand theorems, covering and membership. Tech. rep. Mimeo, Bogazici University, 2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash’s demand game an implementation of the Nash bargaining solution in Debreu–Hurwicz equilibrium.